The Role of Fiqh in Anti-Corruption Education as an Effort to Realize Good Governance in the Context of Halal City - Rahman, Khalid; Hasibuan, Albar Adetary; Madjid, Abdul; Qodri, Lutfi Asnan; Kamal, Sahril (AIBPM Publisher, 2024)
Corruption is an acute problem in Indonesia. The government has made various efforts, including imposing heavy sanctions on corruptors. In the city of Malang in 2018, 41 out of 45 people were accused of corruption. Therefore, Fiqh as a study has become the basis for Halal City in the city of Malang since Mayor Sutiaji since 2022. This study uses library research methods in analyzing the concept of Fiqh in anti-corruption education with a quantitative approach to reveal the understanding of the people of Malang City about the halal city. Data were analyzed using Structural Equation Modeling (SEM). The halal city policy implemented in Malang City still focuses on providing guarantees of halal food and beverages sold in Malang City. Hence, halal city as a habitus still needs more efforts, especially in relation to the attitude and behavior of government officials and society who must represent universal halal values. Halal values that should be cultivated in the city of Malang are a culture of fighting corruption. Starting from the government, both executive, legislative and law enforcement. Then the public rejected the existence of money politics in administrative services in Malang City, as well as money politics during general elections